Simulasi Pengaruh Variasi Sudut Chamfer Forging Terhadap Penyambungan Material Mild Steel Pada Las Gesek Rotari - Muhammad Nafis; Yohanes Yohanes; Ridwan Abdurrahman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The welding process is carried out in the solid phase. The friction welding process that occurs from the direct conversion of mechanical energy into friction into thermal energy. The process of friction between two surface objects in the direction of the direction. The connection process is carried out on the surface with a flame temperature (melting point), so that the connection can be ascertained between the surface of the material being welded and the joints of the same nature. In the previous study, measuring when measuring data when testing, the exact time when loading forging, the temperature at the time of welding and the temperature propagation of the specimen along. Therefore, to find out the problems needed for this, it is necessary to do an evaluation before conducting welding so that we can get groupings or predictions to do welding with good results, and with this simulation it is also expected to be studied according to the temperature of the specimen on welding requirements. From the simulation results, the exact time and temperature for giving an average forging pressure at each angle is 30° (132.27 seconds; 1.070,2 °C), 45° (127.91 seconds; 1.070,1 °C), 60° (123 ,77 seconds; 1.071,2 °C).Keywords : Friction, Steel, Chamfer Interface Area, Forging